Exchange bias in epitaxial Mn2Au (0 0 1)/Fe (0 0 1) bilayers - Sapozhnik, A. A.; Jourdan, Martin; Zabel, Hartmut; Klaeui, M.; Elmers, H-J (Journal of Physics D: Applied Physics, 2019)
A major step to implement antiferromagnetic Mn2Au in spintronics is to understand the exchange bias (EB) mechanism in Mn2Au/ferromagnet bilayers, which can provide an opportunity for reading the magnetic state of Mn2Au via TMR. A very high bulk Néel temperature of Mn2Au (>1500 K) renders its magnetic structure very robust. For this reason, generating an EB by field cooling (FC) in high-quality epitaxial Mn2Au/ferromagnet bilayers is a challenging task. We succeeded in inducing an EB in such systems by tuning the growth conditions of Mn2Au. Our results indicate that the EB effect increases with decreasing atomic order of the Mn2Au films and can reach EB fields up to 200 Oe. This large EB effect reveals the importance of disorder and interfacial pinning in Mn2Au for its appearance.
CRIS-Team Scopus Importer:2023-03-27
Keywords: antiferromagnetic spintronics; epitaxial thin films; exchange bias; magneto-optic Kerr effect (MOKE); Mn2Au